2017
DOI: 10.1111/pan.13141
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylactic reaction to tranexamic acid in an adolescent undergoing posterior spinal fusion

Abstract: Tranexamic acid is an anti-fibrinolytic agent frequently used in pediatric surgery. Common side effects include nausea, flushing, and headache, but in rare instances, it may produce anaphylaxis; with only one previously reported case in a 72-year-old man. We report a case of a delayed anaphylactic reaction in a pediatric patient undergoing posterior spine fusion; and discuss the intraoperative management of the acute event, immunologic confirmation, and subsequent anesthetic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…We agree with Chiem, Ivanova, Jimenez et al that in the face of tranexamic acid being very widely used for any major pediatric surgery where there is a significant risk of hemorrhage that a high level of vigilance should remain to the possibility of a severe allergic reaction occurring either early or late following its administration. Our patient had no cutaneous features of an allergic reaction and normal serum tryptase measurements—highlighting that neither of these observations rule out anaphylaxis.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…We agree with Chiem, Ivanova, Jimenez et al that in the face of tranexamic acid being very widely used for any major pediatric surgery where there is a significant risk of hemorrhage that a high level of vigilance should remain to the possibility of a severe allergic reaction occurring either early or late following its administration. Our patient had no cutaneous features of an allergic reaction and normal serum tryptase measurements—highlighting that neither of these observations rule out anaphylaxis.…”
supporting
confidence: 89%
“…Sir—I wish to report a similar case of a severe anaphylactic reaction to tranexamic acid to that described in the case report by Chiem J, Ivanova I, and Jimenez N . A 13‐year‐old male, 52 kg, with adolescent idiopathic scoliosis presented for elective posterior thoraco‐lumbar spinal fusion.…”
mentioning
confidence: 86%
“…The first case of anaphylactic reaction to TXA reported a 72-year-old man who underwent CABG surgery. 53 In a retrospective study, Michael et al reported that 7.9% of patients have an incidence of convulsive seizures, especially in open heart surgery. 3 Murkin et almentioned that the administration of high dose tranexamic acid 1.3%-3.8% of patients has an incidence of clinical convulsive seizure, especially in older patients in conjunction with cardiopulmonary bypass and open-chamber cardiac surgery.…”
Section: An Adverse Effect Of Txamentioning
confidence: 99%
“…It has a wide safety margin and is rarely associated with hypersensitivity reactions [1]. In humans, common side effects of TXA are mild symptoms including nausea, flushing, vomiting, allergic skin reactions and headache, although anaphylactic shock is rarely reported [1, 2, 4,5,6, 11]. In dogs, there has been no report of adverse reaction to TXA except for vomiting [7].…”
mentioning
confidence: 99%
“…Several reports concerning anaphylactic reaction to TXA have been documented in human beings, but there have been no similar reports in animals [4, 10, 11]. The symptoms of anaphylaxis related to TXA injection were variously reported as cutaneous signs including itching, erythema, and facial angioedema; respiratory disturbances; and cardiovascular collapse such as hypotension, tachycardia, and cardiac arrest [4, 6, 10, 11]. Interestingly, anaphylactic shock such as hypotension and tachycardia occurred after IV administration of TXA in all patients [4, 10, 11].…”
mentioning
confidence: 99%